Catalysis of oxidative protein folding by small-molecule diselenides - Beld, Joris; Woycechowsky, Kenneth J; Hilvert, Donald (Biochemistry (Easton), 2008)
The production of recombinant, disulfide-containing proteins often requires oxidative folding in vitro. Here, we show that diselenides, such as selenoglutathione, catalyze oxidative protein folding by O 2. Substantially lower concentrations of a redox buffer composed of selenoglutathione and the thiol form of glutathione can consequently be used to achieve the same rate and yield of folding as a standard glutathione redox buffer. Further, the low p K a of selenols extends the pH range for folding by selenoglutathione to acidic conditions, where glutathione is inactive. Harnessing the catalytic power of diselenides may thus pave the way for more efficient oxidative protein folding.